2017
DOI: 10.1186/s12864-017-3984-z
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic and transcriptomic studies of HBV-associated liver fibrosis of an AAV-HBV-infected mouse model

Abstract: BackgroundHuman hepatitis B virus (HBV) infection is an important public health issue in the Asia-Pacific region and is associated with chronic hepatitis, liver fibrosis, cirrhosis and even liver cancer. However, the underlying mechanisms of HBV-associated liver fibrosis remain incompletely understood.ResultsIn the present study, proteomic and transcriptomic approaches as well as biological network analyses were performed to investigate the differentially expressed molecular signature and key regulatory networ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 40 publications
0
23
0
1
Order By: Relevance
“…In this regard, in relation to the implication of antioxidants activity against viral replication, it has been also described that antioxidants can suppress virus-induced oxidative stress and reduce RNA virus production 91 . GSTP1, NKEF and TRX are known antioxidant enzymes with implication and up-regulation in RNA-virus infections 92 and rhabdovirus infections 24 , 93 . However, whether these enzymes may contribute to halting or reducing viral replication remains to be studied.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, in relation to the implication of antioxidants activity against viral replication, it has been also described that antioxidants can suppress virus-induced oxidative stress and reduce RNA virus production 91 . GSTP1, NKEF and TRX are known antioxidant enzymes with implication and up-regulation in RNA-virus infections 92 and rhabdovirus infections 24 , 93 . However, whether these enzymes may contribute to halting or reducing viral replication remains to be studied.…”
Section: Discussionmentioning
confidence: 99%
“…These cytokines include TGF-β, platelet-derived growth factor (PDGF), TNF-α, interferons (IFNα/β), and interleukins (IL-1/6/17) [41,42]. Of all the different cytokine mediated pathways, upregulated TGF-B signaling is thought to be the principal fibrogenic pathway that activates HSCs to synthesize fibrogenic materials like collagen and alpha smooth muscle actin (α-SMA) [106][107][108][109]. In HBV-infected patients, the HBx protein has been identified as an activator of cytokine signaling [110], notwithstanding the synergistic effect induced by chronic inflammation, oxidative stress, and hepatocyte loss that triggers the activation of quiescent HSCs into myofibroblasts, which are the main source of ECM production (e.g., collagen 1/111, α-SMA) in the liver [106,107].…”
Section: Mirna Regulating Hbv-induced Fibrosis/cirrhosismentioning
confidence: 99%
“…In order to identify the therapeutic mechanisms of liver fibrosis by AAVshRNA treatment, we next focused on differentially expressed proteins related to oxidative stress, the PPAR signaling pathway, lipid metabolism, and inflammation, which are involved in hepatic fibrosis.Indeed, in our previous study, oxidative stress was found to play an important role in liver fibrosis [45].…”
Section: Verification Of Proteins Associated With Oxidative Stress Anmentioning
confidence: 89%
“…Removal of the causative agent (HBV) by RNA interference (RNAi) is an effective strategy for treating HBV-induced liver fibrosis, whereas inhibition of the TGF-β pathway alone is not effective. Our study showed the advantages of the combinatorial use of shRNAs against both HBV and TGF-β in alleviating liver fibrosis [44,45]. The mechanisms through which RNAi protects against HBV are unclear, and the inhibiting or activating responses of host factors remains elusive.…”
Section: Introductionmentioning
confidence: 85%